Exploring the Dynamics of Propeller Loops in Human Telomeric DNA Quadruplexes Using Atomistic Simulations - Islam, Barira; Stadlbauer, Petr; Gil-Ley, Alejandro; Pérez-Hernández, Guillermo; Haider, Shozeb; Neidle, Stephen; Bussi, Giovanni; Banas, Pavel; Otyepka, Michal; Sponer, Jiri (Journal of chemical theory and computation, 2017)
We have carried out a series of extended unbiased molecular dynamics (MD) simulations (up to 10 μs long, ∼162 μs in total) complemented by replica-exchange with the collective variable tempering (RECT) approach for several human telomeric DNA G-quadruplex (GQ) topologies with TTA propeller loops. We used different AMBER DNA force-field variants and also processed simulations by Markov State Model (MSM) analysis. The slow conformational transitions in the propeller loops took place on a scale of a few μs, emphasizing the need for long simulations in studies of GQ dynamics. The propeller loops sampled similar ensembles for all GQ topologies and for all force-field dihedral-potential variants. The outcomes of standard and RECT simulations were consistent and captured similar spectrum of loop conformations. However, the most common crystallographic loop conformation was very unstable with all force-field versions. Although the loss of canonical γ-trans state of the first propeller loop nucleotide could be related to the indispensable bsc0 α/γ dihedral potential, even supporting this particular dihedral by a bias was insufficient to populate the experimentally dominant loop conformation. In conclusion, while our simulations were capable of providing a reasonable albeit not converged sampling of the TTA propeller loop conformational space, the force-field description still remained far from satisfactory.
Keywords: shluková analýza; DNA; simulace molekulární dynamiky; G-kvadruplexy; Telomere; Water; Cluster Analysis; Humans; sekvence nukleotidů; Base Sequence; lidé; Molecular Dynamics Simulation; telomery; voda; G-Quadruplexes